Новый вид клещей рода Tarsonemus (Trombidiformes, Tarsonemidae) из Туркменистана - Ужевская С.Ф. (Вестник зоологии, 1993)
Tarsonemus sharonovi sp. n. differs from all known species by coxosternal skeleton structure (prosternum shape, tegulae, sejugal apodeme), size and position of chetae VI Sc2, 2a, h, and tarsal chetae Idl, I etc. Holotype and paratype (females) have been collected on Sorghum halepense in Askhabat vicinity (Turkmenistan), deposited in the collection of the Zoology Department, Odessa University.